Solid electrolyte material and battery using same
Patent Information
- Application Number
- JP2022508069
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-18
- Filing Date
- 2020-12-22
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2040-12-22
AI Technical Summary
Existing solid electrolyte materials, such as LiBF4, have low lithium ion conductivity and can generate hydrogen sulfide when exposed to the atmosphere, posing safety concerns and limiting their application in batteries.
A solid electrolyte material composed of Li, Ti, Al, and M (where M is Zr or Mg) with additional anions like F, Cl, Br, I, O, or Se, which provides high lithium ion conductivity and avoids sulfur, ensuring safety by not generating hydrogen sulfide.
The material achieves ionic conductivity of 1×10^-8 S/cm or more, enabling batteries with excellent charge and discharge characteristics and improved safety by preventing hydrogen sulfide generation.
Smart Images

Figure 00000015_0000 
Figure 00000016_0000 
Figure 00000016_0001
Abstract
Description
Solid electrolyte material and battery using the same
[0001] The present disclosure relates to a solid electrolyte material and a battery using the same.
[0002] Patent Document 1 discloses an all-solid-state battery using a sulfide solid electrolyte, and Patent Document 2 discloses LiBF4 as a fluoride solid electrolyte material.
[0003] JP 2011-129312 A JP 2008-277170 A
[0004] An object of the present disclosure is to provide a solid electrolyte material having high lithium ion conductivity.
[0005] The solid electrolyte material of the present disclosure comprises Li, Ti, Al, M, and F, where M is at least one selected from the group consisting of Zr and Mg.
[0006] The present disclosure provides a solid electrolyte material with high lithium ion conductivity.
[0007] FIG. 1 shows a cross-sectional view of a battery 1000 according to the second embodiment. FIG. 2 shows a cross-sectional view of a battery 2000 according to the second embodiment. FIG. 3 shows a schematic diagram of a pressure forming die 300 used to evaluate the ionic conductivity of a solid electrolyte material. FIG. 4 is a graph showing a Cole-Cole plot obtained by measuring the impedance of the solid electrolyte material according to Example 1. FIG. 5 is a graph showing the initial discharge characteristics of the batteries according to Example 1 and Comparative Example 1.
[0008] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings.
[0009] First Embodiment A solid electrolyte material according to a first embodiment contains Li, Ti, Al, M, and F. M is at least one selected from the group consisting of Zr and Mg. The solid electrolyte material according to the first embodiment has high lithium ion conductivity. Here, high lithium ion conductivity is, for example, 1×10 -8 That is, the solid electrolyte material according to the first embodiment has a conductivity of, for example, 1×10 -8 The ionic conductivity may be 100 S / cm or more.
[0010] The solid electrolyte material according to the first embodiment can be used to obtain a battery having excellent charge / discharge characteristics. An example of such a battery is an all-solid-state battery. The all-solid-state battery may be a primary battery or a secondary battery.
[0011] The solid electrolyte material according to the first embodiment desirably does not contain sulfur. A sulfur-free solid electrolyte material does not generate hydrogen sulfide even when exposed to the atmosphere, and is therefore highly safe. The sulfide solid electrolyte disclosed in Patent Document 1 may generate hydrogen sulfide when exposed to the atmosphere.
[0012] The solid electrolyte material according to the first embodiment contains F, and therefore can have high oxidation resistance. This is because F has a high oxidation-reduction potential. On the other hand, F has a high electronegativity, and therefore bonds relatively strongly with Li. As a result, the lithium ion conductivity of a solid electrolyte material containing Li and F is usually low. For example, LiBF4 disclosed in Patent Document 2 has a lithium ion conductivity of 6.67 × 10 -9 LiBF4 has a low ionic conductivity of, for example, 1 × 10 S / cm. LiBF4 is the solid electrolyte material used in Comparative Example 1, which will be described later. In contrast, the solid electrolyte material according to the first embodiment contains Ti, Al, and M in addition to Li and F, and therefore has a low ionic conductivity of, for example, 1 × 10 -8 It can have a high ionic conductivity of 100 S / cm or more.
[0013] In order to increase the ionic conductivity of the solid electrolyte material, the solid electrolyte material according to the first embodiment may contain anions other than F. Examples of such anions are Cl, Br, I, O, S, or Se.
[0014] The solid electrolyte material according to the first embodiment may consist essentially of Li, Ti, Al, M, and F. Here, "the solid electrolyte material according to the first embodiment consists essentially of Li, Ti, Al, M, and F" means that the molar ratio (i.e., molar fraction) of the total amount of substance of Li, Ti, Al, M, and F to the total amount of substance of all elements constituting the solid electrolyte material according to the first embodiment is 90% or more. As an example, the molar ratio may be 95% or more. The solid electrolyte material according to the first embodiment may consist only of Li, Ti, Al, M, and F.
[0015] The solid electrolyte material according to the first embodiment may contain elements that are inevitably mixed in. Examples of such elements are hydrogen, oxygen, or nitrogen. Such elements may be present in the raw material powder of the solid electrolyte material or in the atmosphere for producing or storing the solid electrolyte material.
[0016] In order to further increase the ionic conductivity of the solid electrolyte material, in the solid electrolyte material according to the first embodiment, the ratio of the amount of substance of Li to the total amount of substance of Ti, Al, and M may be 1.33 or more and 3.79 or less.
[0017] To enhance the ionic conductivity of the solid electrolyte material, M may be Zr.
[0018] The solid electrolyte material according to the first embodiment may be represented by the following composition formula (1): Li(4-x-(4-a)y)(Ti 1-x-y Al x M y ) b F6 Formula (1) In Formula (1), a represents the valence of M, and the following mathematical expressions are satisfied: 0<x<1, 0<y<1, 0<(x+y)<1, and 0<b≦1.5. A solid electrolyte material having such a composition has high ionic conductivity.
[0019] In order to increase the ionic conductivity of the solid electrolyte material, the formula: 0.05≦x≦0.9 may be satisfied in formula (1).
[0020] When M is Mg, the formula: 0.33≦x≦0.7 may be satisfied in formula (1) in order to increase the ionic conductivity of the solid electrolyte material.
[0021] The upper and lower limits of the range of x in formula (1) can be defined by any combination selected from the following numerical values: 0.05, 0.1, 0.33, 0.37, 0.5, 0.6, 0.7, and 0.9.
[0022] In order to increase the ionic conductivity of the solid electrolyte material, the formula: 0.05≦y≦0.9 may be satisfied in formula (1).
[0023] When M is Mg, the formula: 0.1≦y≦0.33 may be satisfied in formula (1) in order to increase the ionic conductivity of the solid electrolyte material.
[0024] The upper and lower limits of the range of y in formula (1) can be defined by any combination selected from the following numerical values: 0.05, 0.1, 0.2, 0.26, 0.33, 0.5, 0.8, and 0.9.
[0025] In order to increase the ionic conductivity of the solid electrolyte material, the formula: 0.8≦b≦1.2 may be satisfied in formula (1).
[0026] The upper and lower limits of the range of b in formula (1) can be defined by any combination selected from the numerical values of 0.8, 0.9, 1.0, 1.1, and 1.2.
[0027] The solid electrolyte material according to the first embodiment may be crystalline or amorphous.
[0028] The shape of the solid electrolyte material according to the first embodiment is not limited. Examples of the shape include a needle shape, a sphere shape, or an oval sphere shape. The solid electrolyte material according to the first embodiment may be in the form of particles. The solid electrolyte material according to the first embodiment may be formed into the shape of a pellet or a plate.
[0029] When the solid electrolyte material according to the first embodiment has a particulate (e.g., spherical) shape, the solid electrolyte material may have a median diameter of 0.1 μm or more and 100 μm or less. The median diameter refers to the particle size when the cumulative volume in the volume-based particle size distribution is equal to 50%. The volume-based particle size distribution is measured, for example, by a laser diffraction measurement device or an image analysis device.
[0030] The solid electrolyte material according to the first embodiment may have a median diameter of 0.5 μm or more and 10 μm or less. This allows the solid electrolyte material to have higher conductivity. Furthermore, when the solid electrolyte material according to the first embodiment is mixed with other materials such as active materials, the solid electrolyte material according to the first embodiment and the other materials are well dispersed.
[0031] <Method for Producing Solid Electrolyte Material> The solid electrolyte material according to the first embodiment can be produced by, for example, the following method.
[0032] Raw material powders are prepared and mixed to obtain a desired composition. The raw material powders may be, for example, halides.
[0033] As an example, if the target composition is Li 3.07 Ti 0.27 Al 0.27 Zr 0.27 In the case of F, LiF, TiF, AlF, and ZrF are mixed in a molar ratio of about 3.07:0.27:0.27:0.27. The raw material powders may be mixed in a pre-adjusted molar ratio to offset composition changes that may occur in the synthesis process.
[0034] The raw material powders are reacted with each other mechanochemically (i.e., using a mechanochemical milling method) in a mixing device such as a planetary ball mill to obtain a reactant. The reactant may be fired in a vacuum or in an inert atmosphere. Alternatively, a mixture of the raw material powders may be fired in a vacuum or in an inert atmosphere to obtain a reactant. The firing is preferably carried out, for example, at a temperature of 100°C or higher and 300°C or lower for one hour or longer. In order to suppress compositional changes during firing, the raw material powders are preferably fired in a sealed container such as a quartz tube.
[0035] By these methods, the solid electrolyte material according to the first embodiment can be obtained.
[0036] Second Embodiment A second embodiment will be described below. The matters described in the first embodiment may be omitted.
[0037] The battery according to the second embodiment includes a positive electrode, a negative electrode, and an electrolyte layer. The electrolyte layer is provided between the positive electrode and the negative electrode. At least one selected from the group consisting of the positive electrode, the electrolyte layer, and the negative electrode contains the solid electrolyte material according to the first embodiment. The battery according to the second embodiment has excellent charge / discharge characteristics because it contains the solid electrolyte material according to the first embodiment. The battery may be an all-solid-state battery.
[0038] FIG. 1 shows a cross-sectional view of a battery 1000 according to a second embodiment.
[0039] The battery 1000 according to the second embodiment includes a positive electrode 201, an electrolyte layer 202, and a negative electrode 203. The electrolyte layer 202 is provided between the positive electrode 201 and the negative electrode 203.
[0040] The positive electrode 201 contains positive electrode active material particles 204 and solid electrolyte particles 100 .
[0041] The electrolyte layer 202 contains an electrolyte material, such as a solid electrolyte material.
[0042] The negative electrode 203 contains negative electrode active material particles 205 and solid electrolyte particles 100 .
[0043] The solid electrolyte particles 100 are particles made of the solid electrolyte material according to the first embodiment, or particles containing as a main component the solid electrolyte material according to the first embodiment. Here, the particles containing as a main component the solid electrolyte material according to the first embodiment refer to particles in which the component contained in the largest amount by mass is the solid electrolyte material according to the first embodiment.
[0044] The positive electrode 201 contains a material capable of absorbing and releasing metal ions (e.g., lithium ions). The material is, for example, a positive electrode active material (e.g., positive electrode active material particles 204).
[0045] Examples of positive electrode active materials include lithium-containing transition metal oxides, transition metal fluorides, polyanionic materials, fluorinated polyanionic materials, transition metal sulfides, transition metal oxysulfides, and transition metal oxynitrides. Examples of lithium-containing transition metal oxides include Li(Ni, Co, Al)O, Li(Ni, Co, Mn)O, and LiCoO. In this disclosure, the notation "(Ni, Co, Al)" in a chemical formula indicates at least one element selected from the group of elements in parentheses. That is, "(Ni, Co, Al)" is synonymous with "at least one element selected from the group consisting of Ni, Co, and Al." The same applies to other elements.
[0046] The positive electrode active material particles 204 may have a median diameter of 0.1 μm or more and 100 μm or less. When the positive electrode active material particles 204 have a median diameter of 0.1 μm or more, the positive electrode active material particles 204 and the solid electrolyte particles 100 are well dispersed in the positive electrode 201. This improves the charge / discharge characteristics of the battery 1000. When the positive electrode active material particles 204 have a median diameter of 100 μm or less, the lithium diffusion rate within the positive electrode active material particles 204 improves. This allows the battery 1000 to operate at high power.
[0047] The positive electrode active material particles 204 may have a larger median diameter than the solid electrolyte particles 100. This improves the dispersion state of the positive electrode active material particles 204 and the solid electrolyte particles 100 in the positive electrode 201.
[0048] In order to increase the energy density and output of the battery, in the positive electrode 201, the ratio of the volume of the positive electrode active material particles 204 to the sum of the volume of the positive electrode active material particles 204 and the volume of the solid electrolyte particles 100 may be 0.30 or more and 0.95 or less.
[0049] A coating layer may be formed on at least a portion of the surface of the positive electrode active material particle 204. The coating layer may be formed on the surface of the positive electrode active material particle 204, for example, before mixing with the conductive additive and the binder. Examples of coating materials included in the coating layer include a sulfide solid electrolyte, an oxide solid electrolyte, or a halide solid electrolyte. When the solid electrolyte particle 100 contains a sulfide solid electrolyte, the coating material may contain the solid electrolyte material according to the first embodiment to suppress oxidative decomposition of the sulfide solid electrolyte. When the solid electrolyte particle 100 contains the solid electrolyte material according to the first embodiment, the coating material may contain an oxide solid electrolyte to suppress oxidative decomposition of the solid electrolyte material. Lithium niobate, which has excellent stability at high potentials, may be used as the oxide solid electrolyte. By suppressing oxidative decomposition of the solid electrolyte material, an increase in battery overvoltage can be suppressed.
[0050] To increase the energy density and power output of the battery, the positive electrode 201 may have a thickness of 10 μm or more and 500 μm or less.
[0051] The electrolyte layer 202 contains an electrolyte material. The electrolyte material is, for example, a solid electrolyte material. The electrolyte layer 202 may be a solid electrolyte layer.
[0052] The electrolyte layer 202 may be composed solely of the solid electrolyte material according to the first embodiment. Alternatively, it may be composed solely of a solid electrolyte material different from the solid electrolyte material according to the first embodiment. Examples of solid electrolyte materials different from the solid electrolyte material according to the first embodiment include LiMgX, LiFeX, Li(Al, Ga, In)X, Li(Al, Ga, In)X, or LiI, where X is at least one selected from the group consisting of F, Cl, Br, and I.
[0053] Hereinafter, the solid electrolyte material according to the first embodiment will be referred to as a first solid electrolyte material, and a solid electrolyte material different from the solid electrolyte material according to the first embodiment will be referred to as a second solid electrolyte material.
[0054] The electrolyte layer 202 may contain not only the first solid electrolyte material but also the second solid electrolyte material. The first solid electrolyte material and the second solid electrolyte material may be uniformly dispersed in the electrolyte layer 202. A layer made of the first solid electrolyte material and a layer made of the second solid electrolyte material may be stacked along the stacking direction of the battery 1000.
[0055] FIG. 2 shows a cross-sectional view of a battery 2000 according to a second embodiment.
[0056] 2 , the battery 2000 may include a positive electrode 201, a first electrolyte layer 212, a second electrolyte layer 222, and a negative electrode 203. That is, the electrolyte layer 202 may include the first electrolyte layer 212 and the second electrolyte layer 222. The first electrolyte layer 212 is disposed between the positive electrode 201 and the negative electrode 203. The second electrolyte layer 222 is disposed between the first electrolyte layer 212 and the negative electrode 203.
[0057] In the battery 2000, the first electrolyte layer 212 may contain the solid electrolyte material according to the first embodiment. The solid electrolyte material according to the first embodiment has high oxidation resistance, and therefore can be used without oxidizing the solid electrolyte material contained in the second electrolyte layer 222. As a result, the charge / discharge efficiency of the battery can be improved.
[0058] In the battery 2000, the solid electrolyte material contained in the second electrolyte layer 222 may have a lower reduction potential than the solid electrolyte material contained in the first electrolyte layer 212. This allows the solid electrolyte material contained in the first electrolyte layer 212 to be used without being reduced. As a result, the charge / discharge efficiency of the battery can be improved. For example, when the first electrolyte layer 212 contains the solid electrolyte material according to the first embodiment, the second electrolyte layer 222 may contain a sulfide solid electrolyte to suppress reductive decomposition of the solid electrolyte material.
[0059] To increase the energy density and power output of the battery, the electrolyte layer 202 may have a thickness of 1 μm or more and 1000 μm or less.
[0060] The negative electrode 203 contains a material capable of absorbing and releasing metal ions (e.g., lithium ions). The material is, for example, a negative electrode active material (e.g., negative electrode active material particles 205).
[0061] Examples of the negative electrode active material include a metal material, a carbon material, an oxide, a nitride, a tin compound, or a silicon compound. The metal material may be a single metal or an alloy. An example of the metal material is lithium metal or a lithium alloy. Examples of the carbon material are natural graphite, coke, partially graphitized carbon, carbon fiber, spherical carbon, artificial graphite, or amorphous carbon. From the viewpoint of capacity density, suitable examples of the negative electrode active material are silicon (i.e., Si), tin (i.e., Sn), a silicon compound, or a tin compound.
[0062] The negative electrode active material may be selected in consideration of the reduction resistance of the solid electrolyte material contained in the negative electrode 203. For example, when the negative electrode 203 contains the solid electrolyte material according to the first embodiment, the negative electrode active material may be a material capable of absorbing and releasing lithium ions at 0.27 V or more relative to lithium. Examples of such negative electrode active materials include titanium oxide, indium metal, or a lithium alloy. An example of titanium oxide is Li4Ti5O 12 , LiTiO, or TiO. By using the above-mentioned negative electrode active material, it is possible to suppress the reductive decomposition of the solid electrolyte material according to the first embodiment contained in the negative electrode 203. As a result, it is possible to improve the charge / discharge efficiency of the battery.
[0063] The negative electrode active material particles 205 may have a median diameter of 0.1 μm or more and 100 μm or less. When the negative electrode active material particles 205 have a median diameter of 0.1 μm or more, the negative electrode active material particles 205 and the solid electrolyte particles 100 are well dispersed in the negative electrode 203. This improves the charge / discharge characteristics of the battery. When the negative electrode active material particles 205 have a median diameter of 100 μm or less, the lithium diffusion rate within the negative electrode active material particles 205 is improved. This allows the battery to operate at high power.
[0064] The negative electrode active material particles 205 may have a larger median diameter than the solid electrolyte particles 100. This improves the dispersion state of the negative electrode active material particles 205 and the solid electrolyte particles 100 in the negative electrode 203.
[0065] In order to increase the energy density and output of the battery, in the negative electrode 203, the ratio of the volume of the negative electrode active material particles 205 to the sum of the volume of the negative electrode active material particles 205 and the volume of the solid electrolyte particles 100 may be 0.30 or more and 0.95 or less.
[0066] To increase the energy density and power output of the battery, the negative electrode 203 may have a thickness of 10 μm or more and 500 μm or less.
[0067] At least one selected from the group consisting of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a second solid electrolyte material for the purpose of increasing ionic conductivity, chemical stability, and electrochemical stability.
[0068] The second solid electrolyte material may be a sulfide solid electrolyte.
[0069] Examples of sulfide solid electrolytes include Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, and Li 3.25 Ge 0.25 P 0.75 S4, or Li 10 GeP2S 12 is.
[0070] When the electrolyte layer 202 contains the solid electrolyte material according to the first embodiment, the negative electrode 203 may contain a sulfide solid electrolyte to suppress reductive decomposition of the solid electrolyte material. By covering the negative electrode active material with the electrochemically stable sulfide solid electrolyte, it is possible to suppress contact between the solid electrolyte material according to the first embodiment and the negative electrode active material. As a result, the internal resistance of the battery can be reduced.
[0071] The second solid electrolyte material may be an oxide solid electrolyte.
[0072] Examples of oxide solid electrolytes include: (i) NASICON-type solid electrolytes such as LiTi2(PO4)3 or its elemental substitutions; (ii) perovskite-type solid electrolytes such as (LaLi)TiO3; (iii) Li 14 ZnGeO 16 LISICON-type solid electrolytes such as LiSiO, LiGeO or elemental substitutions thereof; (iv) LiLaZrO 12 or an element-substituted product thereof, or (v) a garnet-type solid electrolyte such as Li3PO4 or an N-substituted product thereof.
[0073] As mentioned above, the second solid electrolyte material may be a halide solid electrolyte.
[0074] Examples of halide solid electrolytes are LiMgX, LiFeX, Li(Al,Ga,In)X, Li(Al,Ga,In)X, or LiI, where X is at least one selected from the group consisting of F, Cl, Br, and I.
[0075] Other examples of halide solid electrolyte materials include Li a Me b Y c X6. Here, a + mb + 3c = 6, and c > 0 are satisfied. Me is at least one selected from the group consisting of metal elements and metalloid elements other than Li and Y. m represents the valence of Me. "Metalloid elements" are B, Si, Ge, As, Sb, and Te. "Metal elements" are all elements included in Groups 1 to 12 of the periodic table (excluding hydrogen) and all elements included in Groups 13 to 16 of the periodic table (excluding B, Si, Ge, As, Sb, Te, C, N, P, O, S, and Se).
[0076] To enhance the ionic conductivity of the halide solid electrolyte material, Me may be at least one selected from the group consisting of Mg, Ca, Sr, Ba, Zn, Sc, Al, Ga, Bi, Zr, Hf, Ti, Sn, Ta, and Nb. The halide solid electrolyte may be LiYCl or LiYBr.
[0077] The second solid electrolyte material may be an organic polymer solid electrolyte.
[0078] An example of the organic polymer solid electrolyte is a compound of a polymer compound and a lithium salt.
[0079] The polymer compound may have an ethylene oxide structure. A polymer compound having an ethylene oxide structure can contain a large amount of lithium salt, and therefore can further increase ionic conductivity.
[0080] Examples of lithium salts include LiPF, LiBF, LiSbF, LiAsF, LiSOCF, LiN(SOCF), LiN(SOCF), LiN(SOCF)(SOCF), or LiC(SOCF). One lithium salt selected from these may be used alone. Alternatively, a mixture of two or more lithium salts selected from these may be used.
[0081] At least one selected from the group consisting of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a non-aqueous electrolyte solution, a gel electrolyte, or an ionic liquid for the purpose of facilitating the exchange of lithium ions and improving the output characteristics of the battery.
[0082] The non-aqueous electrolyte contains a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent.
[0083] Examples of non-aqueous solvents are cyclic carbonate ester solvents, chain carbonate ester solvents, cyclic ether solvents, chain ether solvents, cyclic ester solvents, chain ester solvents, or fluorine-containing solvents. Examples of cyclic carbonate ester solvents are ethylene carbonate, propylene carbonate, or butylene carbonate. Examples of chain carbonate ester solvents are dimethyl carbonate, ethyl methyl carbonate, or diethyl carbonate. Examples of cyclic ether solvents are tetrahydrofuran, 1,4-dioxane, or 1,3-dioxolane. Examples of chain ether solvents are 1,2-dimethoxyethane or 1,2-diethoxyethane. An example of a cyclic ester solvent is γ-butyrolactone. An example of a chain ester solvent is methyl acetate. Examples of fluorine-containing solvents are fluoroethylene carbonate, methyl fluoropropionate, fluorobenzene, fluoroethyl methyl carbonate, or fluorodimethylene carbonate. One non-aqueous solvent selected from these may be used alone, or two or more non-aqueous solvents selected from these may be used in combination.
[0084] Examples of lithium salts include LiPF, LiBF, LiSbF, LiAsF, LiSOCF, LiN(SOCF), LiN(SOCF), LiN(SOCF)(SOCF), or LiC(SOCF). A single lithium salt selected from these may be used alone. Alternatively, a mixture of two or more lithium salts selected from these may be used. The concentration of the lithium salt is, for example, in the range of 0.5 mol / L or more and 2 mol / L or less.
[0085] The gel electrolyte may be a polymer material impregnated with a non-aqueous electrolyte, such as polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, or a polymer having an ethylene oxide bond.
[0086] Examples of cations contained in the ionic liquid are: (i) aliphatic chain quaternary salts such as tetraalkylammonium or tetraalkylphosphonium; (ii) aliphatic cyclic ammoniums such as pyrrolidiniums, morpholiniums, imidazoliniums, tetrahydropyrimidiniums, piperaziniums, or piperidiniums; or (iii) nitrogen-containing heterocyclic aromatic cations such as pyridiniums or imidazoliums.
[0087] An example of an anion contained in an ionic liquid is PF6 - , BF4 - , SbF6 - , AsF6 - , SO3CF3 - , N(SO2CF3)2 - , N(SO2C2F5)2 - , N(SO2CF3)(SO2C4F9) - , or C(SO2CF3)3 - is.
[0088] The ionic liquid may contain a lithium salt.
[0089] At least one selected from the group consisting of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a binder for the purpose of improving adhesion between particles.
[0090] Examples of binders include polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamideimide, polyacrylonitrile, polyacrylic acid, polymethyl ester of acrylic acid, polyethyl ester of acrylic acid, polyhexyl ester of acrylic acid, polymethacrylic acid, polymethyl ester of methacrylic acid, polyethyl ester of methacrylic acid, polyhexyl ester of methacrylic acid, polyvinyl acetate, polyvinylpyrrolidone, polyether, polyethersulfone, hexafluoropolypropylene, styrene-butadiene rubber, and carboxymethyl cellulose. Copolymers can also be used as binders. Examples of such binders include copolymers of two or more materials selected from the group consisting of tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, chlorotrifluoroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid, and hexadiene. Mixtures of two or more materials selected from these may also be used as binders.
[0091] At least one of the positive electrode 201 and the negative electrode 203 may contain a conductive additive to reduce electronic resistance.
[0092] Examples of the conductive additive include: (i) graphites such as natural graphite or artificial graphite, (ii) carbon blacks such as acetylene black or ketjen black, (iii) conductive fibers such as carbon fiber or metal fiber, (iv) carbon fluoride, (v) metal powders such as aluminum, (vi) conductive whiskers such as zinc oxide or potassium titanate, (vii) conductive metal oxides such as titanium oxide, or (viii) conductive polymer compounds such as polyaniline, polypyrrole, or polythiophene. To reduce costs, the conductive additives (i) or (ii) above may be used.
[0093] Examples of the shape of the battery according to the second embodiment include a coin type, a cylindrical type, a square type, a sheet type, a button type, a flat type, and a laminate type.
[0094] The battery according to the second embodiment may be manufactured, for example, by preparing a material for forming a positive electrode, a material for forming an electrolyte layer, and a material for forming a negative electrode, and by using a known method to fabricate a laminate in which the positive electrode, the electrolyte layer, and the negative electrode are arranged in this order.
[0095] Hereinafter, the present disclosure will be described in more detail with reference to examples and comparative examples.
[0096] Example 1 (Preparation of Solid Electrolyte Material) In an argon atmosphere having a dew point of -60°C or less (hereinafter referred to as "dry argon atmosphere"), raw material powders of LiF, TiF4, AlF3, and ZrF4 were prepared in a molar ratio of LiF:TiF4:AlF3:ZrF4 = 3.07:0.27:0.27:0.27. These materials were pulverized and mixed in a mortar. The resulting mixture was milled for 12 hours at 500 rpm using a planetary ball mill. In this way, a powder of a solid electrolyte material according to Example 1 was obtained. The solid electrolyte material according to Example 1 contained Li, 3.07 Ti 0.27 Al 0.27 Zr 0.27 It had a composition represented by F6.
[0097] (Evaluation of Ionic Conductivity) FIG. 3 shows a schematic diagram of a pressure forming die 300 used to evaluate the ionic conductivity of the solid electrolyte material.
[0098] The pressure molding die 300 had an upper punch 301, a frame 302, and a lower punch 303. The frame 302 was made of insulating polycarbonate, and the upper punch 301 and the lower punch 303 were made of electronically conductive stainless steel.
[0099] Using the pressure molding die 300 shown in FIG. 3, the ionic conductivity of the solid electrolyte material of Example 1 was evaluated by the following method.
[0100] In a dry atmosphere having a dew point of −30° C. or less, the powder of the solid electrolyte material according to Example 1 was filled into the inside of the pressure molding die 300. Inside the pressure molding die 300, a pressure of 400 MPa was applied to the solid electrolyte material according to Example 1 using the upper punch 301 and the lower punch 303.
[0101] While the pressure was still applied, the upper punch 301 and the lower punch 303 were connected to a potentiostat (Princeton Applied Research, VersaSTAT4) equipped with a frequency response analyzer. The upper punch 301 was connected to a working electrode and a potential measurement terminal. The lower punch 303 was connected to a counter electrode and a reference electrode. The impedance of the solid electrolyte material was measured by electrochemical impedance measurement at room temperature.
[0102] FIG. 4 is a graph showing a Cole-Cole plot obtained by measuring the impedance of the solid electrolyte material according to Example 1.
[0103] In Fig. 4, the real value of the impedance at the measurement point where the absolute value of the phase of the complex impedance is smallest was considered to be the resistance value for ion conduction of the solid electrolyte material. SE Using the resistance value, the ionic conductivity was calculated based on the following formula (2): σ=(R SE × S / t) -1 ...(2) where σ represents ionic conductivity, and S represents the contact area of the solid electrolyte material with the punch upper portion 301 (equal to the cross-sectional area of the hollow portion of the frame mold 302 in FIG. 3). SE represents the resistance value of the solid electrolyte material in impedance measurement, and t represents the thickness of the solid electrolyte material (i.e., the thickness of the layer formed from the powder 101 of the solid electrolyte material in FIG. 3).
[0104] The ionic conductivity of the solid electrolyte material according to Example 1 measured at 25°C was 2.23 × 10 -6 S / cm.
[0105] (Fabrication of Battery) In a dry argon atmosphere, the solid electrolyte material according to Example 1 and the active material LiCoO2 were prepared in a volume ratio of 30:70. These materials were mixed in an agate mortar. In this way, a positive electrode mixture was obtained.
[0106] Next, LiCl and YCl were prepared in a molar ratio of LiCl:YCl = 3:1. These materials were ground and mixed in a mortar. The resulting mixture was milled for 12 hours at 500 rpm using a planetary ball mill. In this way, a halide solid electrolyte (hereinafter referred to as "LYC") having a composition represented by LiYCl was obtained.
[0107] In an insulating tube having an inner diameter of 9.5 mm, LYC (60 mg), the solid electrolyte material according to Example 1 (26 mg), and the above-described positive electrode mixture (9.1 mg) were stacked in this order. A pressure of 300 MPa was applied to the resulting stack, forming a second electrolyte layer, a first electrolyte layer, and a positive electrode. That is, the first electrolyte layer formed from the solid electrolyte material according to Example 1 was sandwiched between the second electrolyte layer and the positive electrode. The thicknesses of the second electrolyte layer and the first electrolyte layer were 450 μm and 150 μm, respectively.
[0108] Next, metal In (thickness: 200 μm) was laminated on the second electrolyte layer, and a pressure of 80 MPa was applied to the resulting laminate to form a negative electrode.
[0109] Next, current collectors made of stainless steel were attached to the positive and negative electrodes, and current collecting leads were attached to the current collectors.
[0110] Finally, the inside of the insulating cylinder was isolated from the outside atmosphere using an insulating ferrule, and the inside of the cylinder was sealed. In this way, the battery according to Example 1 was obtained.
[0111] (Charge / Discharge Test) Fig. 5 is a graph showing the initial discharge characteristics of the battery according to Example 1. The initial charge / discharge characteristics were measured by the following method.
[0112] The battery according to Example 1 was placed in a thermostatic chamber at 85°C.
[0113] 27 μA / cm 2 The battery according to Example 1 was charged at a current density of 0.02 C until a voltage of 3.6 V was reached. The current density corresponds to a 0.02 C rate.
[0114] Next, 27 μA / cm 2 The battery according to Example 1 was discharged at a current density of 0.1 V until a voltage of 1.9 V was reached.
[0115] As a result of the charge-discharge test, the battery according to Example 1 had an initial discharge capacity of 698 μAh.
[0116] <Examples 2 to 20> (Preparation of solid electrolyte material) In Examples 2 to 15, LiF, TiF, AlF, and ZrF were prepared as raw material powders in a molar ratio of LiF:TiF:AlF:ZrF={6-(4-x)b}:(1-xy)b:xb:yb.
[0117] In Examples 16 to 20, LiF, TiF, AlF, and MgF were prepared as raw material powders in a molar ratio of LiF:TiF:AlF:MgF={6-(4-x-2y)b}:(1-xy)b:xb:yb.
[0118] Except for the above points, the solid electrolyte materials according to Examples 2 to 20 were obtained in the same manner as in Example 1.
[0119] For the solid electrolyte materials according to Examples 2 to 20, the values of x, y, b, and Li / (Ti+Al+M) molar ratio are shown in Table 1.
[0120] (Evaluation of Ion Conductivity) The ion conductivity of the solid electrolyte materials according to Examples 2 to 20 was measured in the same manner as in Example 1. The measurement results are shown in Table 1.
[0121] (Charge-Discharge Test) Using the solid electrolyte materials of Examples 2 to 20, batteries of Examples 2 to 21 were obtained in the same manner as in Example 1.
[0122] The batteries according to Examples 2 to 20 were subjected to charge / discharge tests in the same manner as in Example 1. The batteries according to Examples 2 to 20 were charged and discharged as well as the battery according to Example 1.
[0123] Comparative Example 1: As a solid electrolyte material, Li 3.07 Ti 0.27 Al 0.27 Zr 0.27 LiBF4 was used instead of F6.
[0124] The ionic conductivity of LiBF was measured in the same manner as in Example 1. The ionic conductivity measured at 25°C was 6.67 × 10 -9 S / cm.
[0125] A battery according to Comparative Example 1 was obtained in the same manner as in Example 1, except that LiBF4 was used as the solid electrolyte material.
[0126] A charge-discharge test was carried out on the battery of Comparative Example 1 in the same manner as in Example 1. As a result, the battery of Comparative Example 1 had an initial discharge capacity of 0.01 μAh or less. That is, the battery of Comparative Example 1 was neither charged nor discharged.
[0127] Table 1 shows the solid electrolyte materials in Examples 1 to 20 and Comparative Example 1 and the evaluation results.
[0128]
[0129] <Discussion> The solid electrolyte materials according to Examples 1 to 20 had a melting point of 1×10 -8 On the other hand, the solid electrolyte material according to the comparative example has a high ionic conductivity of 1×10 -8 It has low ionic conductivity of less than S / cm.
[0130] As is clear from a comparison of Examples 2, 4, 5, and 6 with Examples 16, 17, 18, and 19, respectively, the ionic conductivity of the solid electrolyte material is higher when M is Zr than when M is Mg.
[0131] The batteries according to Examples 1 to 20 were all charged and discharged at 85° C. On the other hand, the battery according to Comparative Example 1 was neither charged nor discharged.
[0132] The solid electrolyte materials according to Examples 1 to 20 do not contain sulfur and therefore do not generate hydrogen sulfide.
[0133] As described above, the solid electrolyte material according to the present disclosure is suitable for providing a battery that has high lithium ion conductivity and can be charged and discharged well.
[0134] The solid electrolyte material of the present disclosure is used, for example, in an all-solid-state lithium-ion secondary battery.
[0135] REFERENCE SIGNS LIST 100 Solid electrolyte particles 101 Powder of solid electrolyte material 201 Positive electrode 202 Electrolyte layer 212 First electrolyte layer 222 Second electrolyte layer 203 Negative electrode 204 Positive electrode active material particles 205 Negative electrode active material particles 300 Pressure molding die 301 Upper punch 302 Frame 303 Lower punch 1000 Battery 2000 Battery
Claims
1. A solid electrolyte material comprising Li, Ti, Al, M, and F, wherein M is at least one selected from the group consisting of Zr and Mg.
2. The solid electrolyte material according to claim 1, wherein the ratio of the amount of substance of Li to the total amount of substance of Ti, Al, and M is 1.33 or more and 3.79 or less.
3. Represented by the following compositional formula (1): Li6-(4-x-(4-a)y)b(Ti 1-x-y Al x M y )) b F6 ··· Formula (1) Here, a represents the valence of M, and 0 < x < 1, 0 < y < 1, 0 < (x + y) < 1, and 0 < b ≦ 1.5 are satisfied. The solid electrolyte material according to claim 1 or 2.
4. The solid electrolyte material according to claim 3, wherein the formula: 0.05 ≦ x ≦ 0.9 is satisfied.
5. The solid electrolyte material according to claim 3 or 4, wherein the formula: 0.05 ≦ y ≦ 0.9 is satisfied.
6. The solid electrolyte material according to any one of claims 3 to 5, wherein M is Mg, and the formula: 0.33 ≦ x ≦ 0.7 is satisfied.
7. The solid electrolyte material according to any one of claims 3 to 6, wherein M is Mg, and the formula: 0.1 ≦ y ≦ 0.33 is satisfied.
8. The solid electrolyte material according to any one of claims 3 to 7, wherein the formula: 0.8 ≦ b ≦ 1.2 is satisfied.
9. A battery comprising a positive electrode, a negative electrode, and an electrolyte layer provided between the positive electrode and the negative electrode, wherein at least one selected from the group consisting of the positive electrode, the negative electrode, and the electrolyte layer contains the solid electrolyte material according to any one of claims 1 to 8.
10. The battery according to claim 9, wherein the electrolyte layer includes a first electrolyte layer and a second electrolyte layer, the first electrolyte layer is disposed between the positive electrode and the negative electrode, the second electrolyte layer is disposed between the first electrolyte layer and the negative electrode, and the first electrolyte layer contains the solid electrolyte material.